Miraculous Amalgams: The In Khong Style Murals of the Fourth Reign (1851‒1868) - McBain, Paul (The Journal of the Siam Society, 2025)
In mid-19th century Bangkok, Siamese temple mural art saw the rise of the innovative “In Khong style”, characterized by three-dimensional landscapes and European-style buildings, departing from relatively two-dimensional Buddhist narratives. Proliferating during the Fourth Reign (Rama IV, 1851‒1868), this style extended beyond Khrua In Khong’s documented works. This article argues that the In Khong style was a modern art form unique to Siam, shaped by the development of a class of hired craftsmen inspired by imported wallpaper and prints. Reflecting Siam’s age of wonder and fascination with the West, these murals expressed a reimagined world through fantastical landscapes and structures, rather than merely imitating European forms and techniques.